Processing of Ant Sugar as a Natural Sweetener for Coffee Flavor Variants in Latanza Banyuwangi: Pengolahan Gula Semut Sebagai Natural Sweetener Varian Rasa Kopi di Latanza Banyuwangi - Bachtiar, Riza Rahimi; Purwaningtyas, Ayu; Feveriati, Anggra (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Banyuwangi is one of the coffee and coconut producing centers in East Java Province and nationally. Coconut and coffee productivity has increased from year to year. One of the MSMEs that operates in the field of processing plantation products is CV. Latanza Dua Kelapa which produces ant sugar. Ant sugar comes from coconut sap which is produced in original flavor variants. There are several problems experienced by CV. Latanza Dua Kelapa includes: 1) Making ant sugar which is still done traditionally and 2) Ant sugar products which still do not have other flavor variants (only original flavor variants) so it is necessary to automate the production process and add flavor variants to avoid market saturation. One additional flavor variant that can be produced is a coffee flavor variant. The addition of coffee flavor variants also aims to highlight local wisdom from Banyuwangi district because it is one of the areas famous for producing Robusta Coffee. The aim of this Community Service (PKM) is to utilize coconut and coffee which are abundant in Banyuwangi through the use of automatic equipment in the crystallization process. The product that will be produced is ant sugar with a coffee flavor variant. It is hoped that this new product can be an alternative souvenir for tourists visiting Banyuwangi.